2020
DOI: 10.3390/ijms21249750
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Melatonin Synthesis-Related Indoles in the Turkey Pineal Organ and Its Modification by Monochromatic Light

Abstract: The metabolism of pineal indoles is closely related to alterations in the light and dark phases of a daily cycle. Recent research showed important interspecies differences in the pineal biochemistry, and a strong impact of monochromatic light on many physiological processes in birds. Therefore, the aims of study were to characterize the metabolism of melatonin-synthesis indoles in the pineal organ of the domestic turkey, and to determine the changes occurring in this metabolism under the influence of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
3
0
4
Order By: Relevance
“…Most studies on mechanisms regulating MLT secretion have been performed with chickens ( Robertson and Takahashi, 1988a , b , Nakahara et al, 1997 ; Csernus et al, 1998 , 1999 ; Zawilska et al, 2000 ; Turkowska et al, 2014 ). In this species, environmental light entrains a diurnal rhythm of MLT secretion in both in vivo and in vitro conditions; light acts as both a synchronizing factor in MLT production and an inhibitor of its production ( Takahashi et al, 1980 ; Robertson and Takahashi, 1988b ; Csernus et al, 2005 ; Martyniuk et al, 2020 ). However, rhythmic MLT secretion, albeit of lower amplitude, persists in chicken pinealocytes kept in constant darkness, suggesting that this rhythm is also endogenously driven ( Nakahara et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on mechanisms regulating MLT secretion have been performed with chickens ( Robertson and Takahashi, 1988a , b , Nakahara et al, 1997 ; Csernus et al, 1998 , 1999 ; Zawilska et al, 2000 ; Turkowska et al, 2014 ). In this species, environmental light entrains a diurnal rhythm of MLT secretion in both in vivo and in vitro conditions; light acts as both a synchronizing factor in MLT production and an inhibitor of its production ( Takahashi et al, 1980 ; Robertson and Takahashi, 1988b ; Csernus et al, 2005 ; Martyniuk et al, 2020 ). However, rhythmic MLT secretion, albeit of lower amplitude, persists in chicken pinealocytes kept in constant darkness, suggesting that this rhythm is also endogenously driven ( Nakahara et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время функция иммунной системы рассматривается вкупе с функцией нервной и эндокринной систем в составе многофункциональной, многокомпонентной нейро-иммунно-эндокринной системы регуляции гомеостаза [18]. Установлено, что кора больших полушарий, базальные ядра, задние и передние гипоталамические поля, лимбическая система, ретикулярная формация, ядра шва, миндалевидный комплекс участвуют в регуляции иммунного ответа [19,20]. ГАМК, серотонин, дофамин, глутамат, бета-эндорфин, энкефалины, цитомедины через взаимодействие со специфическими рецепторами на иммунокомпетентных клетках регулируют функциональную активность, пролиферацию и дифференцировку иммунокомпетентных клеток [21].…”
Section: корреляционная матрица между иммунным статусом и показателям...unclassified
“…Клетки микроглиии астроциты являются основными иммунными эффекторными клетками мозга и наряду с цитотоксическими Т-клетками играют важную роль в нейрогенезе и формировании пространственной памяти [23]. В присутствии активирующего стимула клетки микроглии модулируют иммунный ответ, через секрецию фактора некроза опухоли-α (TNF-α), IL-1, IL-4, IL-6, INF-γ [19,21,24].…”
Section: корреляционная матрица между иммунным статусом и показателям...unclassified
See 1 more Smart Citation
“…Melatonin (MLT) and 5-methoxyindole acetic acid (5-MIAA) are detectable in the pineal organs from ED 18 and show significant daily variations in their contents from ED 20. A recently published study [16] demonstrated that a daily cycle of light and dark phases is insufficient to establish a well-entrained daily rhythm of MLT secretion in the pineal organs of 12-week old geese in superfusion culture. Direct pineal photoreception plays a less important role in regulating MLT secretion in the domestic goose than in the chicken [17][18][19][20] and the domestic turkey [21,22]. These differences may reflect dissimilarities in the histological organization and ultrastructure of the pineal organs in these birds [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%